Sub-Saharan Africa's Integration in the Global Financial Markets - Delechat, Corinne (IMF Working Papers; Working Paper, 2009)
The paper uses a unique database covering 44 countries in sub-Saharan Africa (SSA) countries between 2000 and 2007 to study the determinants of the allocation and composition of flows across countries, as well as channels through which private capital flows could affect growth. In our sample, the degree of financial market development is an important determinant of the distribution of capital flows across countries as opposed to property rights institutions. The fairly consistent positive association between net capital flows and growth for SSA countries contrasts with the more pessimistic results of recent studies, though our data do not allow us to make conclusive inferences about a causality relationship.